2020
DOI: 10.3233/jvr-191068
|View full text |Cite
|
Sign up to set email alerts
|

Importance and satisfaction ratings on 38 key employment concerns among African American women with multiple sclerosis

Abstract: OBJECTIVE: This article provides descriptive findings from a sub-sample of 143 female African Americans with multiple sclerosis (MS) who responded to a national survey of the employment concerns of Americans with MS. Respondents evaluated 38 employment concerns items on two dimensions, importance and satisfaction, for the purpose of identifying strengths and weaknesses in the employment policies and practices affecting the labor force participation of African American women with MS. RESULTS: Results revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…These variables are largely missing in studies from European countries with substantial minority populations. In line with what Rumrill et al 39 point out, people with MS from minority groups might be exposed to greater risks of discrimination and barriers.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…These variables are largely missing in studies from European countries with substantial minority populations. In line with what Rumrill et al 39 point out, people with MS from minority groups might be exposed to greater risks of discrimination and barriers.…”
Section: Discussionsupporting
confidence: 67%
“… 35 Several studies showed that the employment rates were low for non-Caucasian Americans with MS. Hispanics, Afro-Americans, and Afro-American women with MS all had low levels of employment in the US. 35 , 38 , 39 In a recent American study on work loss due to the Covid-19 pandemic, it was found that non-Caucasian persons with MS reported work loss to a higher extent than those identifying as white. 33 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations